2016
DOI: 10.1101/079061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational prediction of the tolerance to amino-acid deletion in green-fluorescent protein

Abstract: Proteins evolve through two primary mechanisms: substitution, where mutations alter a protein's amino-acid sequence, and insertions and deletions (indels), where amino acids are either added to or removed from the sequence. Protein structure has been shown to influence the rate at which substitutions accumulate across sites in proteins, but whether structure similarly constrains the occurrence of indels has not been rigorously studied. Here, we investigate the extent to which structural properties known to cov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…7e), though the R 2 is only 0.27. WCN was also the single best predictor of whether a deletion is tolerated in eGFP [17]. The lack of simple correlations between properties and insertion fitness were consistent with our expectation that the fitness effects of insertions have complex origins.…”
Section: Relationship Between Indel Fitness Effects and Tem-1 Sequence/structuresupporting
confidence: 83%
See 1 more Smart Citation
“…7e), though the R 2 is only 0.27. WCN was also the single best predictor of whether a deletion is tolerated in eGFP [17]. The lack of simple correlations between properties and insertion fitness were consistent with our expectation that the fitness effects of insertions have complex origins.…”
Section: Relationship Between Indel Fitness Effects and Tem-1 Sequence/structuresupporting
confidence: 83%
“…They found that the majority of tolerated deletions occurred in loops, while the rest were found equally distributed in helices and β-strands, with the termini of β-strands being more tolerant than the middle. Computational analysis of the EGFP found that structural properties such as relative solvent accessibility and weighted contact number (WCN) can be used to predict tolerance to deletions to some extent [17].…”
Section: Introductionmentioning
confidence: 99%
“…Only two single ΔFlucs (ΔV384 and ΔR387) exhibited a near‐complete loss of activity, demonstrating that loop regions of ×11 Fluc are largely tolerant to single amino acid deletions in loops. Ordinarily deletions in proteins of residues with low residue solvent accessibility (RSA) such as Gly and Pro are better tolerated than larger residues, or those that make fewer contacts (Jackson, Spielman, & Wilke, ). Aside from in the N‐terminal, deletions of Pro (P353 and P359), Gly (G360 and G363), Ala (A361), Val (V362), Leu (L376), and Asp (D377) were best tolerated or enhanced brightness in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…These were then inputted into a python script calc_RSA.py to generate a list of RSA values. Weighted contact numbers (WCN) calculated as described (Jackson et al, ) using script calc_WCN.py. Scripts are made free to use on GitHub page.…”
Section: Methodsmentioning
confidence: 99%
“…It is expected that different structural attributes do not share the same indel dynamics. For example, it was recently shown that for enhanced green fluorescent protein (eGFP), the packing density of a residue, as measured by the weighted contact number (Lin et al, 2008), considerably affects the probability that a single-residue deletion disrupts the protein’s function (Jackson et al, 2017). Relative surface accessibility and secondary structure attributes were also found to affect this probability.…”
Section: Discussionmentioning
confidence: 99%